Musical and performative structure of BTM’s - Moreira Neto, Euclid (Seven Editora, 2023)
Report of how the musical and performative structures of the groups of Traditional Blocks of Maranhão (BTMs) are developed on the island of São Luís, an area considered a metropolitan region of the capital of Maranhão. Each instrument used by the manifestation is related as well as the characters that are used in the performative act by the groups of the category are described, as well as innovation actions practiced today. In this perspective, concepts of popular culture, tradition and how these cultural groups of the carnival field were adapted are discussed.DOI:https://doi.org/10.56238/alookdevelopv1-105